Transcriptional regulatory cascade of LcMYB71 and LcNAC73 affects low-temperature and drought stress response in Lonicera caerulea - Zang, Dandan; Sun, Yan; Zhao, Hengtian (Frontiers in Plant Science, 2023)
The development of stress tolerance is regulated via the transcriptional regulatory networks involving regulatory homeostasis mediated by protein-DNA interactions. It is necessary to identify the upstream regulators of a specific gene to characterize gene functions and the associated transcriptional pathways. LcNAC73 from Lonicera caerulea was characterized to understand the underlying mechanism of low-temperature and drought stress response in L. caerulea. The transient transformation and stable transgenic system were used to produce transgenic L. caerulea plants with overexpressed and silenced LcNAC73, elucidating the effect of LcNAC73 on low-temperature and drought stress tolerance. LcNAC73 positively regulated the proline content and enhanced the scavenging of reactive oxygen species, thus improving tolerance to low-temperature and drought stress. To better understand the transcription pathway of LcNAC73, we cloned the promoter and screened proteins that could interact with the promoter. Using Yeast one-hybrid, electrophoretic mobility shift, and chromatin immunoprecipitation assays, we found that the LcMYB71 protein specifically bound to the promoter of LcNAC73. In addition, LcMYB71 and LcNAC73 had similar expression patterns and tolerance character development under low-temperature and drought stress.Further studies revealed that LcMYB71 and LcNAC73 had similar functions and could improve plant low-temperature and drought tolerance.